Evaluation of Citizen Partner Program in State High School 13 Surabaya - Roesminingsih, Maria Veronika; Handayaningrum, Warih; Husna, Nafi’ Sayyidatul (International Journal for Educational and Vocational Studies, 2020)
The development of education in Indonesia must use at least four basic strategies. Namely, The first is equitable distribution of opportunities for education; the second is relevance; the third is quality improvement, and the fourth is efficiency. Generally, this strategy can be divided into two dimensions, namely education improvement and equity. Development of quality improvement is expected to increase the efficiency, effectiveness and productivity of education. "Dimensions of educational equity are expected to provide equal opportunities in obtaining education for all school ages" (Amri, 2013: 68). In realizing distribution of opportunities to obtain education, Surabaya implements a program for acceptance of new students through the path of community partners. The emergence of this policy is also a proof of the government's commitment in carrying out the mandate of the Constitution regarding 20% of the budget for education. This study uses an evaluation research with a qualitative approach. The main data source in this study was obtained by snowball sampling. Data collection techniques in this study used three techniques, namely observation, interviews, and documentation. State High School 13 Surabaya is one of the schools implementing a citizen partner program. The conclusion from this study states that the implementation of the citizen partner program in State High School 13 Surabaya has not yet been reached because of the discovery of elements of nepotism and lack of socialization resulting in one student having not been affected by the community partner program.